Analisis Penerapan Pembiayaan Mudharabah dan Musyarakah dengan Profit Margin Berbasis Bagi Hasil (Studi Kasus di BMT Makin Amin Kamal) - Nurhasanah, Siti; Qadariyah, Lailatul (Universitas Islam Negeri Alauddin Makassar, 2023)
Mudharabah and Musyarakah financing are types of sharia financing based on the principle of profit sharing. Mudharabah financing is a business collaboration between the provider of funds and the business manager, while musyarakah financing is a business collaboration between two partners who provide funds and manage the business. Profits and losses are shared according to the agreed ratio. Profit sharing based profit margin is profit calculated based on profit sharing obtained from mudharabah and musyarakah financing. This study aims to analyze the application of mudharabah and musyarakah financing with profit sharing-based profit margins at BMT Makin Amin (a sharia microfinance institution located in Kamal District, Bangkalan Regency). This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The data used are primary and secondary data. Primary data will be obtained through in-depth interviews with the management of BMT Makin Amin Kamal. Meanwhile, secondary data will be collected from literature and documents related to the practice of profit sharing-based financing at BMT Makin Amin Kamal. The results of the study show that BMT Makin Amin implements mudharabah and musyarakah financing with profit-sharing-based profit margins in accordance with sharia provisions. Mudharabah and musyarakah financing has a significant contribution to operating income and fluctuated during the study period at BMT Makin Amin.